Theoretical assessment of bridge structural integrity from vibration signature analysis - Ramli, Mohd. Zamri; Ahmad, Baderul Hisham; Abdul Rahman, Azlan (Faculty of Civil Engineering, 2005)
Almost civil engineering structure such as tower, tall buildings and bridges are exposed to vibration. Vibration occurrence on structure can lead to structural damage such as crack and if in large scale it may cause structure failure and collapse. It also can contribute to uncomfortable condition and threat safety to human. So the dynamic response of structure has to be measured and studied to predict the behaviour of structure under vibration to prevent such problems. Vibration monitoring for civil engineering (e.g. bridge, buildings, dams) has gained a lot of interest over the past few years, due to the cheap instrumentation and the development of modern technology. Besides, the dynamic analysis test result provides useful information on the behaviour and condition of the overall structure. This study concentrates on how to model a bridge structure to perform dynamic analysis. The main objective of this study is to determine the natural frequency and mode shape of bridge structure